2011
DOI: 10.4317/medoral.16.e440
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontal disease and bone mineral density in postmenopausal women: A cross sectional study

Abstract: Objectives: Both periodontitis and osteoporosis represent major health problems especially in elderly women. The relationship between the two diseases and oral bone loss is important having significant public health impact in the prevention of morbidity and mortality related to these disorders. The present study was aimed to investigate the possible association between osteoporosis and periodontal disease among postmenopausal women residing in Goa, India. Study design: A complete periodontal examination (all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 16 publications
7
62
1
6
Order By: Relevance
“…The results from this study demonstrated that a significant negative correlation was observed between periodontal disease and truncal bone BMD further confirming the relationship between osteoporosis and periodontal disease [13]. Further research groups studying populations from Jordan [12], India [9], and USA [11] demonstrate various relationships between periodontal disease and osteoporosis. Noteworthy, while a positive correlation is observed in some studies, other studies have failed to demonstrate either a relationship exists or have concluded that osteoporosis is not a causal factor in the development of moderate to severe chronic periodontitis [15,16].…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results from this study demonstrated that a significant negative correlation was observed between periodontal disease and truncal bone BMD further confirming the relationship between osteoporosis and periodontal disease [13]. Further research groups studying populations from Jordan [12], India [9], and USA [11] demonstrate various relationships between periodontal disease and osteoporosis. Noteworthy, while a positive correlation is observed in some studies, other studies have failed to demonstrate either a relationship exists or have concluded that osteoporosis is not a causal factor in the development of moderate to severe chronic periodontitis [15,16].…”
Section: Introductionsupporting
confidence: 84%
“…Interestingly, growing clinical evidence has suggested that a relationship between osteoporosis and periodontal disease exist [8][9][10][11][12][13][14]. In one of the first well-documented studies investigating this relationship, it was found that osteoporosis had no significant effect with respect to plaque and gingival bleeding but was associated with a significantly greater loss of attachment in osteoporotic women [10].…”
Section: Introductionmentioning
confidence: 96%
“…The deficiency of sex steroids, particularly estrogen, is considered to be the main cause of osteoporosis, although there are many other factors involved. 15 Few studies exist that evaluate the relationship between estrogen deficiency and periodontal disease associated with bone loss in rats. 9,10 Thus, the aim of this study was to morphometrically evaluate the influence of different durations of estrogen deficiency on the ligature-induced alveolar bone loss.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…On the other hand, hormonal changes during this period causes women become more susceptible to inflammatory diseases of the supporting tissues of the teeth; especially, if she doesn't regard the oral health, the risk of this disease will increase [8]. Sultan [9] showed in his studies that relation between bone density loss and bone cavity erosion, indicates that loss of bone mass during menopause have been as a serious factor for periodontal disease [9].…”
Section: Introductionmentioning
confidence: 99%